Industrial Growth in Araraquara and São Carlos Region in the First Decades of the Twentieth Century (Revista Brasileira Multidisciplinar, 2015)
This article describes and analyzes the formation of the first manufacturing activities and the industrial growth in Araraquara and São Carlos region in the early twentieth century. It shows that from the development of the coffee economy in the region, were created the initial conditions for the emergence of a variety of industrial transformation activities of goods for local and regional consumption that could survive while the conditions for its operation and reproduction prevailed. However, changes in the state economy after the 1929 crisis brought deep changes in industry course in the region. Classic studies on the industry origin in São Paulo are taken as reference. From a methodological point of view the research that led to this study had an exploratory and investigative nature of primary and secondary sources. The conclusions point to the cyclical nature of regional productive activities, to changes in the production cycle of the region from the 30s, and to the reasons for the survival of some companies that have managed to overcome the initial difficulties and till the XXI century are part of the regional productive structure.
Keywords: Industrial Growth; Industry origin in São Paulo; Coffee and Industry in São Paulo; Industry Origin in Araraquara- São Carlos Region.